Analisis Naskah Drama Lautan Bernyanyi Karya Putu Wijaya: Sebuah Kajian Strukturalisme Drama - Seni Melani; Salwa Sania Adawiah; Dalpa Nurmaulidah; Adita Widara Putra (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Literary works certainly have their own benefits, but to find out these benefits you must first analyze them with special studies, one of which is structural studies. Researchers conducted a structural study of literary works in the form of drama scripts. The researcher used the drama script "Lautan Bernyanyi" by Putu Wijaya as material for analysis in this research because it is unique, coherent in its structure and has moral values ​​that can be used as lessons by readers. This research aims to (1) describe the relationship between the intrinsic elements of the drama script "Lautan Bernyanyi" by Putu Wijaya (2) describe the moral values ​​contained in the drama script. This study used descriptive qualitative method. With data collection steps (1) Reading the drama script "Lautan Bernyanyi" intensively (2) Analyzing the cohesiveness of the intrinsic elements of the drama script (3) Recording data in the form of dialogue texts contained in the drama script (4) Bibliographic methods used as references in the bibliography list. support this research (5) Analyze the moral values ​​in the drama script "Lautan Singing" and describe them. From the results of the analysis carried out on the drama script "Lautan Bernyanyi" by Putu Wijaya, there is a connection between its elements and the moral values ​​instilled can reach the reader.